Gambaran Hemodinamik Pasien pada Pembedahan Laparaskopi dan Laparatomi dengan General Anestesi di RSUD Kardinah Tegal - Cahyani, Regita Lintang; Handayani, Rahmaya Nova; Adriyani, Fauziah Hanum Nur (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Among various surgical procedures, laparotomy and laparoscopy are among the most frequently performed, especially in cases involving abdominal organs. Both procedures use general anesthesia, but there are differences that affect patient stability, particularly regarding hemodynamic aspects such as blood pressure, pulse rate, and oxygen saturation. These factors can stem from organ manipulation during surgery, bleeding, increased intra-abdominal pressure, or the effects of anesthesia. This study aims to describe the hemodynamic conditions of patients during the pre- and intraoperative phases of laparotomy and laparoscopy. Using a comparative quantitative descriptive study design using a cross-sectional approach, the sample consisted of 52 patients, divided into 26 patients undergoing laparotomy and 26 patients undergoing laparoscopy. An observation sheet was used to collect data. The results of observations during the preoperative phase showed that all patients were hemodynamically stable and within the normal range. However, during surgery, laparotomy patients tended to experience a more significant decrease in blood pressure compared to the laparoscopy group, with an average of 107.3/65.65 mmHg. In contrast, in patients undergoing laparoscopy, a more pronounced increase in heart rate was identified, with an average of 73.26 beats per minute. Despite this difference in response, oxygen saturation levels generally remained stable both pre- and intraoperatively in both patient groups.